Ketone Monoester Supplementation Does Not Expedite the Recovery of Indices of Muscle Damage After Eccentric Exercise - Martin-Arrowsmith, Patrick W.; Lov, Jamie; Dai, Jiaying; Morais, José A.; Churchward-Venne, Tyler A. (Frontiers in Nutrition, 2020)
Purpose: The purpose of this study was to evaluate the effects of a ketone monoester supplement on indices of muscle damage during recovery after eccentric exercise. Methods: In a randomized, double-blind, independent group design, 20 moderately active healthy young adults consumed 360 mg per kg-1 bodyweight of a ketone monoester (KET) or energy-matched carbohydrate (CON) supplement twice daily following eccentric exercise (drop jumps). Maximal isometric voluntary contraction (MIVC) torque, counter-movement jump (CMJ) height, and muscle soreness were measured before (PRE), and immediately (POST), 24 h, and 48 h post-exercise. Blood samples were collected for analysis of -hydroxybutyrate (β-OHB), creatine kinase (CK), and select pro- and anti-inflammatory cytokines. Results: Peak blood β-OHB concentration after supplement intake was greater (P < 0.001) in KET (4.4 ± 0.8 mM) vs. CON (0.4 ± 0.3 mM). Exercise increased CK concentration at 24 h and 48 h vs. PRE (time: P < 0.001) with no difference between KET and CON. Exercise reduced MIVC (KET: -19.9 ± 14.6; CON: -22.6 ± 11.1%) and CMJ (KET: -11.0 ± 7.5; CON: -13.0 ± 8.7%) at POST relative PRE; however, there was no difference between KET and CON on the recovery of MIVC at 24 h (KET: -15.4 ± 20.4; CON: -18.7 ± 20.1%) or 48 h (KET: -7.2 ± 21.2; CON: -11.8 ± 20.2%), or CMJ at 24 h (KET: -9.2 ± 11.5; CON: -13.4 ± 10.8) or 48 h (KET: -12.5 ± 12.4; CON: -9.1 ± 11.7). Muscle soreness was increased during post-exercise recovery (time: P < 0.001) with no differences between KET and CON. Monocyte chemoattractant protein-1 was greater (group: P = 0.007) in CON (236 ± 11 pg/mL) vs. KET (187 ± 11 pg/mL). Conclusion: In conclusion, twice daily ingestion of a ketone monoester supplement that acutely elevates blood β-OHB concentration does not enhance the recovery of muscle performance or reduce muscle soreness following eccentric exercise in moderately active, healthy young adults.